Strategy of Agribusiness Development of Chrysanthemum Flower in Pancasari Village, Sukasada District, Buleleng Regency - I Nyoman Rudianta; Anak Agung Ngurah Mayun Wirajaya (Warmadewa University Press, 2018)
This study aims to identify and analyze internal and external factors on the development of chrysanthemum agribusiness in Pancasari Village, and to formulate alternative strategies and to determine the priority of agribusiness development strategy of chrysanthemum flowers in Pancasari Village. Determination of the location of the study using the method